(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The results of the use of adsorbents obtained from rice husks by a special technology in the process of purifying alcohols are presented. The data obtained illustrate the adsorption of organic impurities. It is also shown that the obtained adsorbents are promising in comparison with activated carbon.